Lodestar - Messenger, Shannon (Messenger, Shannon. Keeper of the lost cities, 2017)
Back in the Lost Cities, the threat of war hangs thick in the air, and Sophie Foster isn't sure who she can trust. When she learns that those she loves are in danger, she sets out to uncover the truth of the mysterious symbol that could be the key to saving them before it's too late.